INTERLANGUAGE PROCESS - Novasyari, Ressy (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2020)
Abstract This article describes about the definition of Interlanguage process andinterlanguage process. An interlanguage is an emerging linguistic systemthat has been developed by a learner of a second language (or L2) whohas not become fully proficient yet but is only approximating the targetlanguage: preserving some features of their first language (or L1) inspeaking or writing the target language and creating innovations.Interlanguage is the type of language produced by second- andforeign- language learners who are in the process of learning alanguage. Interlanguage refers to the separateness of a secondlanguage learner’s system, a system that has a structurallyintermediate status between the native and target language.Keywords: Definition of Interlanguage process and Interlanguage proces